Hubungan Komunikasi Teraupetik Perawat Dengan Tingkat Kepuasan Pasien - Putriyanti Sitorus; Weslei Daeli; Bambang Suryadi (NAJ Nursing Applied Journal, 2024)
Therapeutic communication is a nurse-client relationship designed to facilitate the goal of therapy in achieving an optimal and effective level of healing so as to obtain patient satisfaction which can be interpreted as a personal evaluation of services with health service providers. The aim of the research is to determine the relationship between therapeutic communication and the level of patient satisfaction. The research method used in this research is correlation analysis with a cross sectional approach. Sampling used Simple Random Sampling, totaling 50 respondents. Statistical analysis uses the Chi Square Test. Result: The research results showed that 82% of nurses' therapeutic communication was good, 52% of patients were satisfied, 30% were dissatisfied. The p-value of 0.024 < 0.05 shows that there is a significant relationship between therapeutic communication and the level of patient satisfaction and an Odd Ratio of 6.067. The research conclusion is that there is a relationship between nurse therapeutic communication and patient satisfaction levels.